Chlamydia psittaci infection as a cause of respiratory disease in neonatal foals. (25th September 2019) - Gough, S. L.; Carrick, J.; Raidal, S. L.; Keane, S.; Collins, N.; Cudmore, L.; Russell, C. M.; Raidal, S.; Hughes, K. J.
Summary: Background: During 2016–2018, 15 critically ill neonatal foals with acute respiratory distress associated with Chlamydia psittaci infection were presented to three referral hospitals in New South Wales. Chlamydia psittaci has not previously been associated with the development of neonatal respiratory disease. Objectives: To investigate and describe the clinical features and outcome of C. psittaci infection in neonatal foals. Study design: Multicentre retrospective case series. Methods: The clinical, clinicopathological, necropsy and histological features of 15 foals with confirmed C. psittaci infection were reviewed and reported. Results: Thirteen foals with C. psittaci infection died or were subjected to euthanasia within 36 h of hospitalisation and two foals survived to discharge. Findings during post‐mortem examination of nonsurviving foals included bronchopneumonia, pulmonary congestion, hepatic congestion and hepatic inflammation. Detection of C. psittaci was achieved using polymerase chain reaction (PCR) testing of swabs of nasal secretions (4/6) and rectal mucosa (5/7) from live foals, lung tissues of foals at necropsy (11/14) and foetal membranes (4/5). Main limitations: Small numbers of confirmed cases of neonatal C. psittaci infection and inconsistent sampling methods. Conclusions: Chlamydia psittaci should be considered a differential diagnosis for neonatal foals with signs of severe systemic disease, including equine neonatal acute respiratory distress syndrome (EqNARDS). Chlamydia psittaci is a zoonotic pathogen and a personal protective equipment (PPE) should be worn for the management of foals with suspected or confirmed infection.